Single-Bone Forearm Salvage Procedure for a Child with Acquired Radial Clubhand in a Resource Limited Centre: A Case Report - Haniza, Sahdi; Chan, Wai Hoong; Nurul Bahariah, Dollah; Entri, Ajek (Malaysian Orthopaedic Association, 2018)
Acquired radial clubhand deformity can be a consequence of large bone gap left by premature extensive radius osteomyelitis sequestrectomy. Single-bone forearm reconstruction is a salvage procedure when other motionpreserving techniques are not feasible. Here we present a child who developed radial clubhand deformity after an untimely sequestrectomy of radius diaphysis. In view of limited microsurgical .expertise in our centre, single-bone forearm procedure was done utilising simple Kirshner wires to achieve radio-ulnar fusion. The procedure resulted in painfree stable wrist, restoration of hand function and improved cosmesis